Serum Gamma GlutamylTransferase, Amylase and Alkaline Phosphatase activities in kidney diseases. - Najeeb M. Saleem, Mayssoon M. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The study enrolled a total of 78 patients with acute and chronic kidney diseases for evaluation of the activity of enzymes, gamma-glutamyltransferase (GGT), alkaline phosphatase (ALP) and amylase and compared with 42 normal healthy groups with normal albumin, creatinine and other kidney functions test and the samples were obtained from different hospitals in Baghdad.Patients and methods: Three groups of patients were included. The first group consists of 15 patients with acute kidney diseases that occurs over days to weeks in which measurement of GGT, ALP and amylase were performed. Second group consists of 38 patients suffering from acute kidney diseases for 2-3 months in which serum GGT was evaluated .Third group consist of 25 patients with chronic kidney diseases used for estimation of GGT, ALP and amylase and other biochemical parameters, total cholesterol, urea, creatinine, uric acid and total protein.Results: There was statistically highly significant difference in the activity of enzymes GGT, ALP and amylase P< 0.001 for three groups of patients with acute kidney diseases, and there was a remarkable difference in GGT activity with chronic kidney diseases (P < 0.001).Conclusion: Acute and chronic kidney diseases in human was diagnosed by measurement of enzyme GGT, ALP, and amylase activities